The Role of Grandparents in Enhancing Children's Spiritual Intelligence: A Unique Case Study in Demak, Central Java, Indonesia - Mubarok, M. Ali (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study is important to describe the factors underlying the grandparent parenting pattern, how grandparents strengthen children's spiritual intelligence, and how grandparents strengthen children's spiritual intelligence. This study, conducted in the cultural context of Demak, Central Java, Indonesia, uses a qualitative case study approach using interviews, observations, and documentation. The results of this study indicate several factors underlying the occurrence of grandparent parenting patterns, namely the divorce of both parents and the parent's job factor, which causes the care carried out by grandparents. The impact of grandparents in strengthening children's spirituality leads to various outcomes. On the positive side, children exhibit honesty, diligence, regular worship, Quranic studies, mosque attendance, and association with good friends. On the negative side, children may become spoiled and exploit the situation, such as doing work solely for rewards from grandparents. The author recommends that parents and grandparents work together to educate children; if they work together one day, the child will be even better.